Economic Behaviour from a Biological and Psychological Approach - Cifuentes Gómez, Cindy; Delgado Ruiz, Siervo Tulio; González, Jorge Iván (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper explores some principles of economic behaviour from a biological and psychological perspective, through a reflective analysis on the feasibility of understanding economic actions of individuals from a review of features of non-economic sciences. Emotions are emphasized as important factors in decision-making. Understanding these reasons helps improve the design and evaluation of public policies and investment decisions; furthermore, it is shown that the context of inequality and happiness affects the formation of the heuristic judgment.